In memoriam de I. Martín-Baró e I. Ellacuría - Gaborit, Mauricio (ECA: Estudios Centroamericanos, 2000)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 55, No. 625-626, 2000: 1083-1088.